2006
DOI: 10.1111/j.1526-100x.2006.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Dynamics of Plant Communities on Revegetated Motorway Slopes from Southern Spain: Is Hydroseeding Always Needed?

Abstract: The increasing global rate of road construction is leading to a parallel increase of areas of degraded soil conditions and steep slopes that need revegetation. Hydroseeding with commercial seeds of fast-growing grasses and legumes is a common practice in revegetation of motorway slopes. We carried out 3 years of monitoring of vegetation dynamics on hydroseeded and nonhydroseeded motorway slopes (48 slopes) in a maritime Mediterranean zone in Má laga (southern Spain). Our main objectives were to test whether hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 31 publications
7
86
2
2
Order By: Relevance
“…Many revegetation applications seek to stabilize barren slopes as a result of urban development and/or road construction. Among the many slope revegetation options available, hydroseeding has been widely applied on large and steep slopes in temperate climates [1][2][3]. Many slope stability analyses conducted by multi-disciplinary experts show that hydroseeding has become the representative application for damaged slopes in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Many revegetation applications seek to stabilize barren slopes as a result of urban development and/or road construction. Among the many slope revegetation options available, hydroseeding has been widely applied on large and steep slopes in temperate climates [1][2][3]. Many slope stability analyses conducted by multi-disciplinary experts show that hydroseeding has become the representative application for damaged slopes in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in Mediterranean climates such as in Spain and Italy related to the vegetation variables have focused on the growth of herbs and shrubs [56,57]; otherwise, in temperate climates such as in South Korea, China, and Japan attempts were made at introducing tree usage to protect damaged slopes [1,5,58]. However, their studies, regardless of regional areas, found that leguminous, compositae, and graminaceous plants could adapt a revegetated slope well [6]. This study also showed similar results but we suggested that excessive dominance by a specific species such as Artemisia princeps var.…”
Section: Vegetation Propertiesmentioning
confidence: 99%
“…Slope revegetation works have been widely implemented on large and steep slopes in temperate zones [6,11,12]. However, revegetated slopes frequently fail due to heavy rain and drought [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matesanz et al, 2006). Thus, despite the successful use of planting 70 as a restoration technique for gypsum habitats (e.g.…”
mentioning
confidence: 99%